RELIABILITY AND VALIDITY ANALYSIS OF ADOLESCENT SELF-CONCEPT QUESTIONNAIRES IN CHILDREN'S ORPHANAGES - Nuroh Siti Maryam; Aas Saomah (OPTIMA: Journal Of Guidance and Counseling, 2022)
Positive self-concept is fundamental to individual development because it can improve social skills, self-confidence, self-ideals that match expectations, and respect for oneself. The purpose of this study is to measure the validity and reliability for the instrument of adolescent self-concept in child care institutions. The study was conducted in 2022, involving 61 adolescents living in nursing homes with a distribution of 21 men and 40 women. The research approach used is quantitative with 10 question items and a 5-point Likert scale as an alternative answer. Analysis of reliability and validity using Rasch with the help of the Winstep application. The results of the study found that Cronbach's Alpha value was 0.43 which was in the weak category. Then, the results of the person reliability test have a value of 0.32 as an indicator of the consistency of respondents' answers, including in the weak category. From the results of the analysis, the item reliability value is 0.80 which is in the good category. Thus, the self-concept of adolescents living in orphanages can be measured using this instrument